Pemanfaatan Permainan Dakon Bervisi Sets Dalam Menanamkan Karakter Siswa Selama Pembelajaran Jarak Jauh - Ela Suryani; Kartika Yuni Purwanti; Fiktina Vifri Ismiriyam (CV. Ulil Albab Corp, 2022)
The SETS vision dakon game is a form of traditional game combined with a learning process by linking science, environment, technology, and society. With the SETS vision dakon game, it is hoped that teachers will be able to instill character values ​​during distance learning because this game can be done at home. The method used is community development through the following stages: 1) preparation; 2) introduction; 3) implementation; 4) monitoring; and 5) evaluation. The results of this PkM show that the character values ​​that have been embedded in the sixth grade students of SDN Susukan are 1) honest as much as 90.9% in the very good category, 2) intelligent as much as 63.6% in the good category, 3) fair as much as 77, 2% in good category, 4) cooperation as much as 86.3% in very good category, 5) firm as much as 68.1% in good category, 6) imagination as much as 59% with good enough category, 7) ambitious as much as 100% with very good category, 8) brave as much as 81.8% with very good category, and 9) attention as much as 86.3% with very good category.